POLLINATION ECOLOGY OF TRIUMFETTA RHOMBOIDEA (TILIACEAE) - Solomon Raju, A. J.; Sandhya Rani, D. (Annali di Botanica, 2017)
In Triumfetta rhomboidea, the floral characteristics such as showy petals, nectar and pollen, short period of anthesis schedule, self-compatibility, brief period of stigma receptivity, medium pollen/ovule ratio and delayed autonomous selfing suggest that it is facultative autogamous with the option kept open for outcrossing. The natural fruit set and seed set rates reflect the functionality of this breeding system. T. rhomboidea flowers are actinomorphic and conspicuously yellow. Despite the existence of five nectaries at the base of ovary, nectar is secreted in traces only. The pollen is copiously produced at plant level and it is a source of protein and amino acids. Bees use both nectar and pollen while wasps and butterflies use only nectar; all effect pollination. A nymphalid butterfly, Junonia orithya uses this plant as a larval host plant. Animals and humans disperse dry, indehiscent fruits effectively during dry season. Fruits expose seeds only after the decomposition of fruit coat during rainy season and then the seeds germinate and establish new plants.